Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s11259-006-3347-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Tetracycline-Resistant and Susceptible Pasteurellaceae in the Nasopharynx of Loose Group-Housed Calves

Abstract: The aim of the present study was to determine which Pasteurella and Mannheimia species are present in the upper respiratory tract of healthy calves with no history of antimicrobial treatment prior to sampling. The presence of subpopulations of tetracycline-resistant Pasteurellaceae was also investigated. Nasal swabs from 61 loose group-housed, clinically healthy calves, 1 to 4 months old, from 16 dairy herds were inoculated aerobically on a selective medium (Columbia agar with 5% ovine blood and 16 mg/L bacitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
4
22
2
Order By: Relevance
“…Increase in resistance against antibiotics in both P. multocida and M. haemolytica isolates have been reported [27,28]. In our study, according to the antimicrobial susceptibility test results, chloramphenicol (100%), sulfamethoxazole (89.1%) and tetracycline (84.4%) were the most effective drugs, whereas ampicilin (53.1%) was the only intermediate drug.…”
Section: Discussionsupporting
confidence: 53%
“…Increase in resistance against antibiotics in both P. multocida and M. haemolytica isolates have been reported [27,28]. In our study, according to the antimicrobial susceptibility test results, chloramphenicol (100%), sulfamethoxazole (89.1%) and tetracycline (84.4%) were the most effective drugs, whereas ampicilin (53.1%) was the only intermediate drug.…”
Section: Discussionsupporting
confidence: 53%
“…Swabs were stored in Cary Blair transport medium (BD Canada, Inc., Mississauga, ON, Canada) at 4°C prior to processing, as described by Klima et al (2011). Briefly, swabs were vortexed in 0.7 mL of brain heart infusion (BHI) broth, and a 100-μL aliquot of the suspension was cultured on tryptic soy agar (TSA) plates containing 5% sheep blood and 15 μg/mL of bacitracin (Dalynn Biologicals, Inc., Calgary, AB, Canada) at 37°C for 24 h (Catry et al, 2006). Isolates displaying morphology indicative of Mannheimia were subcultured (conditions as above) from each plate and tested for catalase and oxidase.…”
Section: Methodsmentioning
confidence: 99%
“…Another phenotypic approach to the question of transmission is assessment of antimicrobial resistance. Catry et al found tetracycline-resistant P. multocida in the nasopharynx of 5 calves on 1 farm, while no resistant P. multocida were found in the other 56 calves from 15 farms (Catry et al, 2006). No tetracycline had been used on any farms.…”
Section: Epidemiology Of P Multocida Pneumoniamentioning
confidence: 99%